2004
DOI: 10.1038/sj.ijir.3901188
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal penile tumescence and rigidity (NPTR) findings in spinal cord injured men with erectile dysfunction

Abstract: This prospective study aimed at determining whether nocturnal penile tumescence and rigidity (NPTR) findings correlate to the neurologic disorders in spinal cord injured (SCI) patients suffering from erectile dysfunction (ED). A total of 25 acute SCI male patients with post-traumatic ED underwent neurological, electrophysiological and urodynamic examinations, respectively, as well as NPTR recordings. The mean value for rigidity (R), tumescence (T) and duration (D) during NTPR tests were 83.3%, 3.3 cm, 6.4 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Both men and women with UMN lesions affecting the sacral spinal segments have reflex genital arousal. Men with SCI and UMN syndrome are more likely to have reflex erections with projectile ejaculation [2,[17][18][19]. They will be more responsive to phosphodiesterase inhibitors for reliable erections [20,21], and to PVS for ejaculation [2,22,23] than men with LMN syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Both men and women with UMN lesions affecting the sacral spinal segments have reflex genital arousal. Men with SCI and UMN syndrome are more likely to have reflex erections with projectile ejaculation [2,[17][18][19]. They will be more responsive to phosphodiesterase inhibitors for reliable erections [20,21], and to PVS for ejaculation [2,22,23] than men with LMN syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Nocturnal penile tumescence (NPT) is known to be involved in cavernous oxygenation and to suppress TGF‐β1‐induced cavernous fibrosis by increasing oxygen tension [19]. SCI patients have abnormal results on the NPT test, and patients with lesions on the sacral erection center show the most disturbed NPT recordings, with reduced rigidity, tumescence, and duration [20]. It has also been reported in animal models of cavernous nerve injury that increases in hypoxia‐inducible factor‐1α, a transcription factor related to hypoxia, and TGF‐β1 are noted in the corpus cavernosum tissue [11,12,21].…”
Section: Discussionmentioning
confidence: 99%
“…Nocturnal penile tumescence (NPT) can regulate oxygen-required biological processes to protect the integrity of the corpora cavernosa ( 74 ). Although the exact regulatory mechanism of NPT is still unclear, some studies have shown that NPT may be related to neurovascular mechanisms and hormone regulation ( 75 ). A diminished or an absence of erections is thought to result from a decrease in REM sleep in patients with OSA ( 76 ).…”
Section: Methodsmentioning
confidence: 99%